Interprofessional education in the clinical learning environment: a mixed-methods evaluation of a longitudinal experience in the primary care setting. Issue 6 (2nd November 2022) - Miselis, Heather H.; Zawacki, Stacey; White, Susan; Yinusa-Nyahkoon, Leanne; Mostow, Carol; Furlong, Janice; Mott, Katherine K.; Kumar, Anika; Winter, Michael R.; Berklein, Flora; Jack, Brian
ABSTRACT: Team collaboration in our healthcare workforce is necessary to effectively address multifaceted medical and social needs, especially for those impacted by systemic inequities. Effective interprofessional practice and education models including curricula are needed to prepare a practice ready healthcare workforce for team collaboration. Most healthcare trainee interprofessional experiences take place episodically in classroom settings. However, creating a culture that supports team-based learning and interprofessional clinical practice requires teaching skills (e.g., communication, collaboration, shared decision-making, coordination of care) longitudinally in the clinical setting. A weekly interprofessional clinic for patients/clients with chronic health conditions was organized in three primary care practices. Trainees from nutrition, social work, medicine, and physician assistant programs worked with supervising clinicians from each field. Surveys, interviews, and focus groups assessed the effects of interprofessional education and training in the primary care setting. Results show the longitudinal experiential IPE program significantly improved knowledge, attitudes, skills, and values addressing key interprofessional competencies. Qualitative results complement survey data and highlight key themes addressing patient-centered care and team dynamics. These findings demonstrate the importance of longitudinal, immersive team-based interprofessional training in the clinical learning environment.